"If We Can Change the Culture, I Hope We Won’t Need to Say Me Too": Disclosures of Sexual Victimization as a Form of Social Activism - Bleeker, Kacy (American journal of criminal justice, 2023)
The emergence of online social movements, such as #MeToo, has created a unique arena in which both hegemonic discourse and pro-social discourse exist simultaneously. Prior research has found that #MeToo has elicited engagement which negates traditional rape myths and has encouraged disclosure (Andalibi et al., 2016). This is particularly important in the realm of sexual victimization, as rates of disclosure remain largely underreported, due to factors such as self-blame and fear of judgment or retaliation (Starzynski et al., 2005). However, no current research has examined the context of engagement of online disclosures related to #MeToo and whether it provides an avenue for increased disclosure. Thus, the current study seeks to examine the way in which user engagement influences disclosures of sexual victimization.